Windows Server 2008 terminal services resource kit - Anderson, Christa (Microsoft Press, 2009)
In-depth and comprehensive, this Resource Kit delivers the information you need to set up, deploy, and manage a Terminal Services farm using Windows Server® 2008. You get authoritative technical insights from Terminal Services experts, including guidance from members of the Microsoft® product team-along with essential scripts and resources on CD. Get expert advice on how to: Install and configure role services, and learn how they support business casesApply best practices for securing terminal servers and authorizing executablesUse Group Policy to con.